A comparison of communication strategies employed by high proficiency students and low proficiency students of SMK Taee, Serian in completing their English speaking tasks / Susanna Dalton Doel - Dalton Doel, Susanna (2013)
This study investigated the communication strategies employed by form six learners of different proficiency levels; high and low at SMK Taee, a rural school in Serian district. This study also looked into the differences or similarities in strategies employed by learners who were grouped according to their proficiency level. Lastly, it also aimed to look at the communication strategies employed by learners of different proficiency levels when placed in mixed-groups of learners. Data elicited through the adapted OCSI questionnaire and an actual MUET speaking question as the English speaking task of choice was used to identify communication strategies used. The questionnaire was administered to 100 learners; meanwhile another 32 learners were identified to complete the speaking task. The results indicate that both, high as well as low proficiency learners perceived that they mostly employ Social Affective strategies in completing speaking task. The speaking task showed that both learners tend to employ similar communication strategies; however they differed in the degree of incorporating the communication strategies. Meanwhile, when placed in mixed-groups of learners, the data showed that low proficiency learners tend to use lesser communication strategies in completing their English speaking task. From these findings, it helped in giving awareness to both the teachers and learners the use of communication strategies and how it may well help ease communication. In addition, teachers would be able to identify ways to assist learners in improving their speaking skills by introducing various communication strategies that they could employ in completing their speaking tasks and in overcoming communication difficulties.